UPAYA MENINGKATKAN SELF ESTEEM DALAM PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) PADA SISWA KELAS II DI SDN PENDEM 01 BATU - Ni Made Putu Meianti; Rohmad Widodo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Success in learning mathematics is not only influenced by students’ cognitive abilities, but also by affective abilities, namely self-esteem. However, based on observations made, it was found that the self- esteem of grade II students of SDN Pendem 01 Batu was still low. This study aims to determine the increase in students' self-esteem in learning mathematics after implementing the Problem Based Learning (PBL) learning model. This study is a Classroom Action Research (CAR) which was carried out in two cycles, each consisting of the planning, implementation, observation, and reflection stages. At the pre-cycle stage, students' self-esteem was relatively low, with only 33.33% of students in the high category. However, after the implementation of the actions in cycles I and II, there was a significant increase. In cycle I, the percentage of students with high self-esteem increased to 57.57%, and in cycle II it reached 84.85%. After going through two cycles, the level of student learning achievement had met the predetermined completeness standards. Therefore, the research process was considered sufficient and was stopped in cycle II. Based on the results obtained, it can be concluded that there was an increase in self-esteem of class II students at SDN Pendem 01 Batu using the PBL model.